Avaliação da distorção linear em estruturas métalicas de próteses sobre implantes: fundidas em peça única e em segmentos soldados a laser e através da soldagem convencional (brasagem) - Costa, Elza Maria Valadares da [UNESP] (2001)
Prosthesis above osseointegrated implants requires an accurate criterion of manufacture. So, in an edentulous mandibular arch, constructed with chromium steel, five analogous were fixed, parallels, with distance of 10 mm measured of center to center. Above these gold cylinders were positioned and screwed with a torque of 10 N/m. In the next follow, fifteen over structures were fabricated and divided in tour groups: CG - Passive adaptation of gold cylinders; MG - Monobloc casting; BG - Casting in segments after brasing; LG - Casting in segments after laser welding. The structures were observed with measures microscope and the data noted in specific table. The measures done in two points (left and right) in the buccal and lingual surfaces of the interface of the cylinder/analogous set in the x and y-axis. The statistics analysis (ANOVA) showed significant statistics differences, on y-axis, among groups: LG group was superior to BG and this was superior to MG group and on x-axis only MG was superior to others groups (when we studied distortion.)